Application of Simple Additive Weighting Method for Determination of Toddler Nutrition Status - Badrul, Mohammad; Rusdiansyah, Rusdiansyah; Budihartanti, Cahyani (Sinkron : jurnal dan penelitian teknik informatika, 2019)
The nutritional status of children under five is measured by age, weight and height. The weight and height variables are presented in the form of three anthropometric indicators namely weight by age, height by age, and weight by height. By using these indicators the Cipadu-Kreo health center sometimes determines the nutritional status of children under five years of age. Therefore the simple additive weighting (SAW) method is able to decide the nutritional status of toddlers by adding a toddler's body mass index variable, so as to produce the right and valid decision. Then from 20 samples of toddlers categorizing by age group. Obtained the nutritional status results there are 1 toddler get a SAW value of 0.44 with poor nutritional status, 3 toddlers with undernourished status, 8 toddlers with excess nutrition status and 8 toddlers with a balanced nutrition status with the highest SAW value with a value